Stress: better coping associated with lower tau in amyloid positive cognitively unimpaired older adults - Arenaza-Urquijo, Eider (Dryad, 2020)
Objective: Research in animals has shown that chronic stress exacerbates
tau pathology. In humans, psychological stress has been associated with
higher risk of Alzheimer’s disease (AD) clinical syndrome. The objective
of this cross-sectional study was to assess the hypothesis that stress
coping ability (assessed via the “Brief Resilience Scale” [BRS]) is
associated with tau burden and to evaluate whether these associations
differed by sex and amyloid status (A+/A-) in cognitively unimpaired older
adults (CU). Methods: We included 225 CU participants (mean age:
70.4±10.2, 48% females) enrolled in the population-based Mayo Clinic Study
of Aging who completed the BRS and underwent amyloid-PET (PIB-PET) and
tau-PET (AV1451-PET). We fitted multiple regression and ANCOVA models to
assess the associations between BRS and tau-PET and the interaction with
amyloid status and sex. We focused on entorhinal cortex (ERC) tau burden,
and also performed voxel-wise analyses. Age, sex, education, depression
and anxiety were considered as covariates. Results: Higher stress coping
ability was associated with lower tau burden in the medial temporal lobe
(including ERC), occipito-temporal and cuneal/precuneal cortices. The
association was present in both A+ and A- but weaker in A- CU older
adults. There was an interaction between amyloid status and stress coping
ability that was restricted to the medial temporal lobe tau such that A+
CU older adults with lower stress coping abilities showed higher tau.
There were no significant interactions between stress coping and sex.
Conclusions: A faster termination of the stress response (higher coping
ability) may limit the negative effects of stress on tau
deposition.  Conversely, lower stress coping ability may be an
early sign of accumulating tau pathology. Longitudinal studies are
warranted to clarify whether stress mechanisms act to exacerbate tau
pathology or tau influences stress-related brain mechanisms and lowers the
ability to cope with stress.